2003
DOI: 10.2307/3583209
|View full text |Cite
|
Sign up to set email alerts
|

The Norplant Experience in Zaria: A Ten-Year Review

Abstract: Norplant is an effective, long-acting, reversible, progestin-only contraceptive that provides protection for up to five years. The aim of this review is to ascertain the response of family planning clients in Zaria to Norplant. In Nigeria, Family Health International started pre-introductory clinical research on Norplant in 1985 at five sites including Zaria. Since the conclusion of the study, Norplant services have been maintained, but no attempt has been made to report the response of this largely Hausa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Further, no data on continuation of contraceptive use were collected beyond nine months postpartum. However, studies from other countries indicate that continuation rate for hormonal implants are high [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 94%
“…Further, no data on continuation of contraceptive use were collected beyond nine months postpartum. However, studies from other countries indicate that continuation rate for hormonal implants are high [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 94%
“…These results provide insights into the effect of religious beliefs on contraceptive use in rural Nigeria. Explicitly, the predominant religion in the Northern region of the country is Islam which highly disapproves of contraceptive use while the Catholic Christian denomination, which objects to the use of modern contraceptives, is prevalent in the South East Zone (Oye-Adeniran et al , 2005; Haggi, 2003).…”
Section: Predictors Of the Use Of Family Planning In Rural Nigeriamentioning
confidence: 99%
“…These differences are probably due to social, economic, educational, and religious factors [6]. Previous studies by Ekewmpu [7] and Haggi [8], both from Zaria Northern Nigeria, showed an increase in the number of clients swapping from one method of contraceptive to another with a trend towards Norplant and injectable over the last 20 years. As Nigeria strives to achieve the goals of the millennium declaration particularly the reduction of maternal mortality, one of the key interventions is the promotion and usage of effective family planning services [9].…”
Section: Introductionmentioning
confidence: 99%